PERANAN STAY AT HOME DAD DALAM MEMBENTUK KELUARGA SEHAT DAN HARMONIS - Cindy Widhiastuti; Maria Dwi Yanika Hesti Nugraha (Universitas Bunda Mulia, 2013)
The role of stay at home dad in Indonesia, especially in the big city such as Jakarta, it was not a new thing, but status of stay at home dad was emerging where role or traditional system could not be applied to the families in this city. Now, the housewife was not longer could be a central decision to decide the daily life activities to be a healthy family, there was any stay at home dad took one of that part, as a caretaker and figure of mother. This topic was anaylized by using theoretical literature descriptive analysis. Subject in this topic was father who did as a stay at home dad. As a result of this study, based on theoretical literature analysis, showed that role as stay at home dad gave the best role to build a healthy and harmonic family, including nursing, deciding and separating the role, especially family in Indonesia. Keywords : stay at home dad, family, healthy family